# 7.4E: Series Solutions Near an Ordinary Point II (Exercises)

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$

( \newcommand{\kernel}{\mathrm{null}\,}\) $$\newcommand{\range}{\mathrm{range}\,}$$

$$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$

$$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$

$$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$

$$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\id}{\mathrm{id}}$$

$$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\kernel}{\mathrm{null}\,}$$

$$\newcommand{\range}{\mathrm{range}\,}$$

$$\newcommand{\RealPart}{\mathrm{Re}}$$

$$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$

$$\newcommand{\Argument}{\mathrm{Arg}}$$

$$\newcommand{\norm}[1]{\| #1 \|}$$

$$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$

$$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\AA}{\unicode[.8,0]{x212B}}$$

$$\newcommand{\vectorA}[1]{\vec{#1}} % arrow$$

$$\newcommand{\vectorAt}[1]{\vec{\text{#1}}} % arrow$$

$$\newcommand{\vectorB}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vectorC}[1]{\textbf{#1}}$$

$$\newcommand{\vectorD}[1]{\overrightarrow{#1}}$$

$$\newcommand{\vectorDt}[1]{\overrightarrow{\text{#1}}}$$

$$\newcommand{\vectE}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash{\mathbf {#1}}}}$$

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

$$\newcommand{\avec}{\mathbf a}$$ $$\newcommand{\bvec}{\mathbf b}$$ $$\newcommand{\cvec}{\mathbf c}$$ $$\newcommand{\dvec}{\mathbf d}$$ $$\newcommand{\dtil}{\widetilde{\mathbf d}}$$ $$\newcommand{\evec}{\mathbf e}$$ $$\newcommand{\fvec}{\mathbf f}$$ $$\newcommand{\nvec}{\mathbf n}$$ $$\newcommand{\pvec}{\mathbf p}$$ $$\newcommand{\qvec}{\mathbf q}$$ $$\newcommand{\svec}{\mathbf s}$$ $$\newcommand{\tvec}{\mathbf t}$$ $$\newcommand{\uvec}{\mathbf u}$$ $$\newcommand{\vvec}{\mathbf v}$$ $$\newcommand{\wvec}{\mathbf w}$$ $$\newcommand{\xvec}{\mathbf x}$$ $$\newcommand{\yvec}{\mathbf y}$$ $$\newcommand{\zvec}{\mathbf z}$$ $$\newcommand{\rvec}{\mathbf r}$$ $$\newcommand{\mvec}{\mathbf m}$$ $$\newcommand{\zerovec}{\mathbf 0}$$ $$\newcommand{\onevec}{\mathbf 1}$$ $$\newcommand{\real}{\mathbb R}$$ $$\newcommand{\twovec}[2]{\left[\begin{array}{r}#1 \\ #2 \end{array}\right]}$$ $$\newcommand{\ctwovec}[2]{\left[\begin{array}{c}#1 \\ #2 \end{array}\right]}$$ $$\newcommand{\threevec}[3]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \end{array}\right]}$$ $$\newcommand{\cthreevec}[3]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \end{array}\right]}$$ $$\newcommand{\fourvec}[4]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}$$ $$\newcommand{\cfourvec}[4]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}$$ $$\newcommand{\fivevec}[5]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}$$ $$\newcommand{\cfivevec}[5]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}$$ $$\newcommand{\mattwo}[4]{\left[\begin{array}{rr}#1 \amp #2 \\ #3 \amp #4 \\ \end{array}\right]}$$ $$\newcommand{\laspan}[1]{\text{Span}\{#1\}}$$ $$\newcommand{\bcal}{\cal B}$$ $$\newcommand{\ccal}{\cal C}$$ $$\newcommand{\scal}{\cal S}$$ $$\newcommand{\wcal}{\cal W}$$ $$\newcommand{\ecal}{\cal E}$$ $$\newcommand{\coords}[2]{\left\{#1\right\}_{#2}}$$ $$\newcommand{\gray}[1]{\color{gray}{#1}}$$ $$\newcommand{\lgray}[1]{\color{lightgray}{#1}}$$ $$\newcommand{\rank}{\operatorname{rank}}$$ $$\newcommand{\row}{\text{Row}}$$ $$\newcommand{\col}{\text{Col}}$$ $$\renewcommand{\row}{\text{Row}}$$ $$\newcommand{\nul}{\text{Nul}}$$ $$\newcommand{\var}{\text{Var}}$$ $$\newcommand{\corr}{\text{corr}}$$ $$\newcommand{\len}[1]{\left|#1\right|}$$ $$\newcommand{\bbar}{\overline{\bvec}}$$ $$\newcommand{\bhat}{\widehat{\bvec}}$$ $$\newcommand{\bperp}{\bvec^\perp}$$ $$\newcommand{\xhat}{\widehat{\xvec}}$$ $$\newcommand{\vhat}{\widehat{\vvec}}$$ $$\newcommand{\uhat}{\widehat{\uvec}}$$ $$\newcommand{\what}{\widehat{\wvec}}$$ $$\newcommand{\Sighat}{\widehat{\Sigma}}$$ $$\newcommand{\lt}{<}$$ $$\newcommand{\gt}{>}$$ $$\newcommand{\amp}{&}$$ $$\definecolor{fillinmathshade}{gray}{0.9}$$

## Q7.3.1

In Exercises 7.3.1-7.3.12 find the coefficients $$a_0$$,…, $$a_N$$ for $$N$$ at least $$7$$ in the series solution $$y=\sum_{n=0}^\infty a_nx^n$$ of the initial value problem.

1. $$(1+3x)y''+xy'+2y=0,\quad y(0)=2,\quad y'(0)=-3$$

2. $$(1+x+2x^2)y''+(2+8x)y'+4y=0,\quad y(0)=-1,\quad y'(0)=2$$

3. $$(1-2x^2)y''+(2-6x)y'-2y=0,\quad y(0)=1,\quad y'(0)=0$$

4. $$(1+x+3x^2)y''+(2+15x)y'+12y=0,\quad y(0)=0,\quad y'(0)=1$$

5. $$(2+x)y''+(1+x)y'+3y=0,\quad y(0)=4,\quad y'(0)=3$$

6. $$(3+3x+x^2)y''+(6+4x)y'+2y=0,\quad y(0)=7,\quad y'(0)=3$$

7. $$(4+x)y''+(2+x)y'+2y=0,\quad y(0)=2,\quad y'(0)=5$$

8. $$(2-3x+2x^2)y''-(4-6x)y'+2y=0,\quad y(1)=1,\quad y'(1)=-1$$

9. $$(3x+2x^2)y''+10(1+x)y'+8y=0,\quad y(-1)=1,\quad y'(-1)=-1$$

10. $$(1-x+x^2)y''-(1-4x)y'+2y=0,\quad y(1)=2,\quad y'(1)=-1$$

11. $$(2+x)y''+(2+x)y'+y=0,\quad y(-1)=-2,\quad y'(-1)=3$$

12. $$x^2y''-(6-7x)y'+8y=0,\quad y(1)=1,\quad y'(1)=-2$$

## Q7.3.2

13. Do the following experiment for various choices of real numbers $$a_0$$, $$a_1$$, and $$r$$, with $$0<r<1/\sqrt2$$.

1. Use differential equations software to solve the initial value problem $(1+x+2x^2)y''+(1+7x)y'+2y=0,\quad y(0)=a_0,\quad y'(0)=a_1, \tag{A}$ numerically on $$(-r,r)$$. (See Example 7.3.1.)
2. For $$N=2$$, $$3$$, $$4$$, …, compute $$a_2$$, …, $$a_N$$ in the power series solution $$y=\sum_{n=0}^\infty a_nx^n$$ of (A), and graph $T_N(x)=\sum_{n=0}^N a_nx^n\nonumber$ and the solution obtained in (a) on $$(-r,r)$$. Continue increasing $$N$$ until there’s no perceptible difference between the two graphs.

14. Do the following experiment for various choices of real numbers $$a_0$$, $$a_1$$, and $$r$$, with $$0<r<2$$.

1. Use differential equations software to solve the initial value problem $(3+x)y''+(1+2x)y'-(2-x)y=0,\quad y(-1)=a_0,\quad y'(-1)=a_1, \tag{A}$ numerically on $$(-1-r,-1+r)$$. (See Example 7.3.2). Why this interval?)
2. For $$N=2$$, $$3$$, $$4$$, …, compute $$a_2,\dots,a_N$$ in the power series solution $y=\sum_{n=0}^\infty a_n(x+1)^n\nonumber$ of (A), and graph $T_N(x)=\sum_{n=0}^N a_n(x+1)^n\nonumber$ and the solution obtained in (a) on $$(-1-r,-1+r)$$. Continue increasing $$N$$ until there’s no perceptible difference between the two graphs.

15. Do the following experiment for several choices of $$a_0$$, $$a_1$$, and $$r$$, with $$r>0$$.

1. Use differential equations software to solve the initial value problem $y''+3xy'+(4+2x^2)y=0,\quad y(0)=a_0,\quad y'(0)=a_1, \tag{A}$ numerically on $$(-r,r)$$. (See Example 7.3.3.)
2. Find the coefficients $$a_0$$, $$a_1$$, …, $$a_N$$ in the power series solution $$y=\sum_{n=0}^\infty a_nx^n$$ of (A), and graph $T_N(x)=\sum_{n=0}^N a_nx^n\nonumber$ and the solution obtained in (a) on $$(-r,r)$$. Continue increasing $$N$$ until there’s no perceptible difference between the two graphs.

16. Do the following experiment for several choices of $$a_0$$ and $$a_1$$.

1. Use differential equations software to solve the initial value problem $(1-x)y''-(2-x)y'+y=0,\quad y(0)=a_0,\quad y'(0)=a_1, \tag{A}$ numerically on $$(-r,r)$$.
2. Find the coefficients $$a_0$$, $$a_1$$, …, $$a_N$$ in the power series solution $$y=\sum_{n=0}^Na_nx^n$$ of (A), and graph $T_N(x)=\sum_{n=0}^N a_nx^n\nonumber$ and the solution obtained in (a) on $$(-r,r)$$. Continue increasing $$N$$ until there’s no perceptible difference between the two graphs. What happens as you let $$r\to 1$$?

17. Follow the directions of Exercise 7.3.16 for the initial value problem $(1+x)y''+3y'+32y=0,\quad y(0)=a_0,\quad y'(0)=a_1.\nonumber$

18. Follow the directions of Exercise 7.3.16 for the initial value problem $(1+x^2)y''+y'+2y=0,\quad y(0)=a_0,\quad y'(0)=a_1.\nonumber$

## Q7.3.3

In Exercises 7.3.19-7.3.28 find the coefficients $$a_{0},...a_{N}$$ for $$N$$ at least $$7$$ in the series solution $y=\sum_{n=0}^{\infty}a_{n}(x-x_{0})^{n}\nonumber$ of the initial value problem. Take $$x_{0}$$ to be the point where the initial conditions are imposed.

19. $$(2+4x)y''-4y'-(6+4x)y=0,\quad y(0)=2,\quad y'(0)=-7$$

20. $$(1+2x)y''-(1-2x)y'-(3-2x)y=0,\quad y(1)=1,\quad y'(1)=-2$$

21. $$(5+2x)y''-y'+(5+x)y=0,\quad y(-2)=2,\quad y'(-2)=-1$$

22. $$(4+x)y''-(4+2x)y'+(6+x)y=0,\quad y(-3)=2,\quad y'(-3)=-2$$

23. $$(2+3x)y''-xy'+2xy=0,\quad y(0)=-1,\quad y'(0)=2$$

24. $$(3+2x)y''+3y'-xy=0,\quad y(-1)=2,\quad y'(-1)=-3$$

25. $$(3+2x)y''-3y'-(2+x)y=0,\quad y(-2)=-2,\quad y'(-2)=3$$

26. $$(10-2x)y''+(1+x)y=0,\quad y(2)=2,\quad y'(2)=-4$$

27. $$(7+x)y''+(8+2x)y'+(5+x)y=0,\quad y(-4)=1,\quad y'(-4)=2$$

28. $$(6+4x)y''+(1+2x)y=0,\quad y(-1)=-1,\quad y'(-1)=2$$

## Q7.3.4

29. Show that the coefficients in the power series in $$x$$ for the general solution of $(1+\alpha x+\beta x^2)y''+(\gamma+\delta x)y'+\epsilon y=0\nonumber$ satisfy the recurrrence relation $a_{n+2}=-{\gamma+\alpha n\over n+2}\,a_{n+1}-{\beta n(n-1)+\delta n+\epsilon\over(n+2)(n+1)}\, a_n.\nonumber$

30.

1. Let $$\alpha$$ and $$\beta$$ be constants, with $$\beta\ne0$$. Show that $$y=\sum_{n=0}^\infty a_nx^n$$ is a solution of $(1+\alpha x+\beta x^2)y''+(2\alpha+4\beta x)y'+2\beta y=0 \tag{A}$ if and only if $a_{n+2}+\alpha a_{n+1}+\beta a_n=0,\quad n\ge0. \tag{B}$ An equation of this form is called a second order homogeneous linear difference equation. The polynomial $$p(r)=r^2+\alpha r+\beta$$ is called the characteristic polynomial of (B). If $$r_1$$ and $$r_2$$ are the zeros of $$p$$, then $$1/r_1$$ and $$1/r_2$$ are the zeros of $P_{0}(x)=1+\alpha x+\beta x^{2}\nonumber$
2. Suppose $$p(r)=(r-r_1)(r-r_2)$$ where $$r_1$$ and $$r_2$$ are real and distinct, and let $$\rho$$ be the smaller of the two numbers $$\{1/|r_1|,1/|r_2|\}$$. Show that if $$c_1$$ and $$c_2$$ are constants then the sequence $a_n=c_1r_1^n+c_2r_2^n,\quad n\ge0\nonumber$ satisfies (B). Conclude from this that any function of the form $y=\sum_{n=0}^\infty (c_1r_1^n+c_2r_2^n)x^n\nonumber$ is a solution of (A) on $$(-\rho,\rho)$$.
3. Use (b) and the formula for the sum of a geometric series to show that the functions $y_1={1\over1-r_1x}\quad\mbox{ and }\quad y_2={1\over1-r_2x}\nonumber$ form a fundamental set of solutions of (A) on $$(-\rho,\rho)$$.
4. Show that $$\{y_1,y_2\}$$ is a fundamental set of solutions of (A) on any interval that does’nt contain either $$1/r_1$$ or $$1/r_2$$.
5. Suppose $$p(r)=(r-r_1)^2$$, and let $$\rho=1/|r_1|$$. Show that if $$c_1$$ and $$c_2$$ are constants then the sequence $a_n=(c_1+c_2n)r_1^n,\quad n\ge0\nonumber$ satisfies (B). Conclude from this that any function of the form $y=\sum_{n=0}^\infty (c_1+c_2n)r_1^nx^n\nonumber$ is a solution of (A) on $$(-\rho,\rho)$$.
6. Use (e) and the formula for the sum of a geometric series to show that the functions $y_1={1\over1-r_1x}\quad\mbox{ and }\quad y_2={x\over(1-r_1x)^2}\nonumber$ form a fundamental set of solutions of (A) on $$(-\rho,\rho)$$.
7. Show that $$\{y_1,y_2\}$$ is a fundamental set of solutions of (A) on any interval that does not contain $$1/r_1$$.

31. Use the results of Exercise 7.3.30 to find the general solution of the given equation on any interval on which polynomial multiplying $$y''$$ has no zeros.

1. $$(1+3x+2x^2)y''+(6+8x)y'+4y=0$$
2. $$(1-5x+6x^2)y''-(10-24x)y'+12y=0$$
3. $$(1-4x+4x^2)y''-(8-16x)y'+8y=0$$
4. $$(4+4x+x^2)y''+(8+4x)y'+2y=0$$
5. $$(4+8x+3x^2)y''+(16+12x)y'+6y=0$$

## Q7.3.5

In Exercises 7.3.32-7.3.38 find the coefficients $$a_{0}, ..., a_{N}$$ for $$N$$ at least $$7$$ in the series solution $$y=\sum_{n=0}^{\infty} a_{n}x^{n}$$ of the initial value problem.

32. $$y''+2xy'+(3+2x^2)y=0,\quad y(0)=1,\quad y'(0)=-2$$

33. $$y''-3xy'+(5+2x^2)y=0,\quad y(0)=1,\quad y'(0)=-2$$

34. $$y''+5xy'-(3-x^2)y=0,\quad y(0)=6,\quad y'(0)=-2$$

35. $$y''-2xy'-(2+3x^2)y=0,\quad y(0)=2,\quad y'(0)=-5$$

36. $$y''-3xy'+(2+4x^2)y=0,\quad y(0)=3,\quad y'(0)=6$$

37. $$2y''+5xy'+(4+2x^2)y=0,\quad y(0)=3,\quad y'(0)=-2$$

38. $$3y''+2xy'+(4-x^2)y=0,\quad y(0)=-2,\quad y'(0)=3$$

## Q7.3.6

39. Find power series in $$x$$ for the solutions $$y_1$$ and $$y_2$$ of $y''+4xy'+(2+4x^2)y=0\nonumber$ such that $$y_1(0)=1$$, $$y'_1(0)=0$$, $$y_2(0)=0$$, $$y'_2(0)=1$$, and identify $$y_1$$ and $$y_2$$ in terms of familiar elementary functions.

## Q7.3.7

In Exercises 7.3.40-7.3.49 find the coefficients $$a_{0}, ..., a_{N}$$ for $$N$$ at least $$7$$ in the series solution $y=\sum_{n=0}^{\infty} a_{n}(x-x_{0})^{n}\nonumber$ of the initial value problem. Take $$x_{0}$$ to be the point where the initial conditions are imposed.

40. $$(1+x)y''+x^2y'+(1+2x)y=0,\quad y(0)-2,\quad y'(0)=3$$

41. $$y''+(1+2x+x^2)y'+2y=0,\quad y(0)=2,\quad y'(0)=3$$

42. $$(1+x^2)y''+(2+x^2)y'+xy=0,\quad y(0)=-3,\quad y'(0)=5$$

43. $$(1+x)y''+(1-3x+2x^2)y'-(x-4)y=0,\quad y(1)=-2,\quad y'(1)=3$$

44. $$y''+(13+12x+3x^2)y'+(5+2x),\quad y(-2)=2,\quad y'(-2)=-3$$

45. $$(1+2x+3x^2)y''+(2-x^2)y'+(1+x)y=0,\quad y(0)=1,\quad y'(0)=-2$$

46. $$(3+4x+x^2)y''-(5+4x-x^2)y'-(2+x)y=0,\quad y(-2)=2,\quad y'(-2)=-1$$

47. $$(1+2x+x^2)y''+(1-x)y=0,\quad y(0)=2,\quad y'(0)=-1$$

48. $$(x-2x^2)y''+(1+3x-x^2)y'+(2+x)y=0,\quad y(1)=1,\quad y'(1)=0$$

49. $$(16-11x+2x^2)y''+(10-6x+x^2)y'-(2-x)y,\quad y(3)=1,\quad y'(3)=-2$$

This page titled 7.4E: Series Solutions Near an Ordinary Point II (Exercises) is shared under a CC BY-NC-SA 3.0 license and was authored, remixed, and/or curated by William F. Trench via source content that was edited to the style and standards of the LibreTexts platform.